2016
DOI: 10.1097/mib.0000000000000966
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk for Inflammatory Bowel Disease Is a Determinant of Crohnʼs Disease Development in Chronic Granulomatous Disease

Abstract: Background Approximately one third to one half of children with chronic granulomatous disease (CGD) develop gastrointestinal inflammation characteristic of idiopathic inflammatory bowel disease (IBD), usually Crohn’s disease (CD). We hypothesized that overall IBD genetic risk, determined by IBD genetics risk score (GRS), might in part determine IBD development in CGD. Methods We reviewed medical records to establish IBD diagnoses in CGD subjects seen at NIAID. IBD risk SNP genotypes were determined using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…The rs254560_AG SNP in the C5orf66 gene on chromosome 5 found in this study is similar to genes such as CCND280, GLI381, or RB1CC182, which have been described as regulatory CNS proteins that modify transcriptional activity and contribute to brain growth trajectory changes at different biological levels, ranging from cellular changes, brain organization differences and complex phenotypic traits (Kuhlwilm and Boeckx, 2019). The weights of common IBD risk alleles are significant determinants during chronic granulomatosis diseases (CGD) (Huang et al, 2016). Based on general linear models, gray matter (GM) alterations caused by SNPs and Early Adverse Life events (EALs) are predictive of IBS.…”
Section: The Snps Associated With the Central Nervous System In Irritsupporting
confidence: 55%
“…The rs254560_AG SNP in the C5orf66 gene on chromosome 5 found in this study is similar to genes such as CCND280, GLI381, or RB1CC182, which have been described as regulatory CNS proteins that modify transcriptional activity and contribute to brain growth trajectory changes at different biological levels, ranging from cellular changes, brain organization differences and complex phenotypic traits (Kuhlwilm and Boeckx, 2019). The weights of common IBD risk alleles are significant determinants during chronic granulomatosis diseases (CGD) (Huang et al, 2016). Based on general linear models, gray matter (GM) alterations caused by SNPs and Early Adverse Life events (EALs) are predictive of IBS.…”
Section: The Snps Associated With the Central Nervous System In Irritsupporting
confidence: 55%
“…Recent findings demonstrate the role of NADPH oxidase complex in regulating gut immunity, regardless of susceptibility to infections . Furthermore, additional genetic factors are determinant in CGD‐IBD development, such as common IBD risk alleles …”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, additional genetic factors are determinant in CGD-IBD development, such as common IBD risk alleles. 8 Despite new insights into the pathophysiology and clinical characterization of CGD-IBD, the management of the disease is still based on experience with polygenic conventional IBD. Nonetheless, specific features of CGD-IBD must be considered, namely the increased risk of immunosuppressant agents, the risks of anesthesia/sedation for endoscopy procedures in patients with respiratory impairment, and the option of "definitive" therapeutic intervention with hematopoietic stem cell transplantation (HSCT).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of mucosal bridges is a known phenomenon seen in Crohn’s disease [ 21 – 24 ], but pathology only reported nonspecific granulomatous inflammation, not in keeping with the classic histologic findings of Crohn’s disease. Although the risk of IBD is elevated in patients with CGD [ 25 , 26 ], our gastroenterologist colleagues felt that the absence of autoimmune disease in both the patient’s and donor’s past medical history was not in keeping with an autoimmune inflammatory bowel disease. Verification with the donor registry has confirmed that the donor has not experienced any gastrointestinal complications to date.…”
Section: Discussionmentioning
confidence: 99%